Predação de ninhos de tartarugas marinhas e avaliação de métodos de mitigação nas praias da Barreira do Inferno, Parnamirim/RN - Carmo, Hayane Montenegro de Aquino (2021)
Of the seven species of sea turtles on the planet, five occur in Brazil and are on the IUCN Red List of Endangered Species. As sea turtles are migratory, feeding routinely in the waters of one country and spawning on the beaches of another, all nations must work together to protect species. Therefore, understanding the activity of predators of sea turtle nests threatened with extinction is one of the necessary factors for planning species conservation strategies. This dissertation, composed of four chapters. The first provides a general introduction to sea turtles and nest predation, one of the main natural threats to these populations. In order to minimize nest predation in the Barreira do Inferno Launch Center (CLBI) area, Parnamirim / RN, Brazil, the second chapter deals with an extensive bibliographic review, which has 57 articles. Identifying the prevalence of carnivorous mammals as predators and better effectiveness of non-lethal mitigation methods. In the third chapter, the survey of nest predations in CLBI was carried out, using historical data from TAMAR between the seasons of 2005/2006 until 2017/2018. Predatory activity in the area has shown high levels (above 50%) in recent seasons, with the fox (Cerdocyon thous) as the main predator species, followed by the armadillo peba (Euphractus sexcinctus). In the fourth chapter, carried out on the spot, five different methods were tested to mitigate the predation of sea turtle nests in the CLBI area facing the fox (Cerdocyon thous): control, guide and stake, galvanized screen, pepper powder and flag. During the experiment, there was a decrease in the percentage of predation to 33%. It was observed that the flag and the screen had less occurrences of predation. In addition, fox visitations have decreased over the life of the nest, as opposed to the digging and predation that are more intense in the post-laying and hatching of the nest. The results of this work underscore the importance of monitoring efforts in the study area for the conservation and management of the hawksbill turtle (Eretmochelys imbricata) population.